Experimental determination of times, amplitudes, and lengths of cycles of water droplet deformation in air; Technical Physics Letters; Vol. 41, iss. 2 - Volkov R. S. Roman Sergeevich; Vysokomornaya O. V. Olga Valeryevna; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2015, 2015)
Title screen